Monochorionic Diamniotic Vasa Previa Pregnancy: A Medical Student Perspective - Joshua M. Samuel; Fatima Ali; Jonathan Faro; Jonathan D. Baum (Case Reports in Obstetrics and Gynecology)
Monochorionic diamniotic twins and vasa previa are uncommon. We present a case that was followed from ultrasound diagnosis to delivery.